Pengembangan Aplikasi Booking Online Pasien Rawat Jalan Rumah Sakit Berbasis Android - I Wayan Widi Karsana; Putu Andhika Kurniawijaya (Yayasan Kita Menulis, 2022)
Registration services for outpatients that are simple and fast are one of the efforts to improve the quality of service to patients who will seek treatment at the hospital. The strategy adopted by the hospital is to utilize information technology to support services, especially the flow of outpatient registration which will later affect patient satisfaction. One of the strategies implemented by hospitals in the current digital era is to implement a computer-based registration system, but in practice there are still many obstacles and the use of the information system is not optimal where there are still many queues and buildup of patients seeking treatment. This study aims to develop an online outpatient booking application that will make it easier for patients to register for outpatient treatment online. This application is expected to make it easy for patients to register outpatient care without having to come directly to the hospital directly. Patients only need to book a polyclinic through the application and check in when they come to the hospital to get a queue number at the intended polyclinic. It is hoped that this application will shorten service time and reduce patient queues.